Relações públicas estratégicas: mapeamento de públicos - Correia, Carolina Vitória de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The present work intends to analyze the Public Relations as strategy way, evidencing the function of this professional for the appropriate development of the company's strategic plan, basing on the public mapping, a study which deepens the features of each interest group to the organization, listing the points of interest and the performance of each public, exalting the strategic characteristics between public and organization. For this will be done a demonstration of the application of Fabio Franças's theory applied to SNTalent Company. The study of public allows the identification of needs and preferences of each group, which allows creating communication strategies more directed and more prosperous and lasting relations, becoming competitive advantages among this context where the information is fast and the media drive markets constantly. Therefore, SNTalent company will be used as way to verify the theory presented combined with exploratory descriptive research for obtaining subsidies to compare the of relationship with different publics of the institution

O presente trabalho pretende analisar as Relações Públicas de forma estratégia, evidenciando o papel do profissional dessa área para a adequada elaboração do plano estratégico da empresa, embasando-se no mapeamento de públicos, um estudo que aprofunda as características de cada grupo de interesse para a organização, elencando os pontos de interesse e a performance de cada público, exaltando as características estratégicas entre públicos e organização. Para isso será feita uma demonstração da aplicação da teoria de Fábio França à empresa SNTalent. O estudo dos públicos possibilita a identificação das necessidades e das preferências de cada grupo, o que permite a criação de estratégias de comunicação mais direcionadas e relacionamentos mais prósperos e duradouros, tornando-se diferenciais competitivos em meio a este contexto onde as informações são rápidas e os meios de comunicação impulsionam os mercados constantemente
Keywords: Redes sociais; Relações publicas; Comunicação; Estrategia; Social Networks